The Sop Senerek Potential as a Gastronomic Tourist Attraction - Cornelia, Florentina Arga Bhuwana; Sidiq, Muhammad Fajar; Maulidima, Putradji (Journal of Tourism Education, 2023)
Sop Senerek is one of the gastronomic and culinary treasures full of historical narratives of the people of Magelang, Central Java since long time ago. The lack of academic literacy and knowledge of tourists perspective towards sop senerek is the main impetus in this research. The research location was taken in the Borobudur area, Magelang, Central Java. Sop Senerek has the opportunity to become a gastronomic tour that is integrated with the tourist attraction of Borobudur Temple and the surroundings areas. The method in this article overview uses the qualitative descriptive method. The results of this study indicate that further studies of the attractiveness of Sop Senerek and the involvement of nine helix will encourage and increase tourist interest in visiting the Borobudur Temple area to experience an integrated gastronomic tourism experience.